1989
DOI: 10.1159/000460999
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological and Clinical Study of Transaminase Levels and Hepatitis B Antibodies in 1,100 Blood Donors

Abstract: In order to provide epidemiological and clinical information on surrogate testing of blood donations, the respective prevalences of serum hepatitis B virus (HBV) markers and elevated transaminase levels were studied in 1,100 blood donors according to their geographic origin and socioeconomic level. The frequency of serum HBV markers varied as a function of HBV endemicity in the country of origin; however, it was inversely correlated (p<0.05) to the socioeconomic level of the donors, even in those originating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, PCR by its high sensitivity may be detecting viremia less than the infective dose. HBV DNA was also found in 5 of 247 donors negative for all serological markers of HBV infection and normal ALT in France [3]. In the only other study from India, in which HBV DNA was detected in 24% of 126 HBsAg-negative blood donors by PCR [14], a good correlation was reported between HBV DNA positivity and anti-HBc; however, ALT was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PCR by its high sensitivity may be detecting viremia less than the infective dose. HBV DNA was also found in 5 of 247 donors negative for all serological markers of HBV infection and normal ALT in France [3]. In the only other study from India, in which HBV DNA was detected in 24% of 126 HBsAg-negative blood donors by PCR [14], a good correlation was reported between HBV DNA positivity and anti-HBc; however, ALT was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The exact relationship of ALT elevation with incidence of PTH-B in different countries with low, intermediate and high prevalence rates of HBV is not clear. In France 2.7% of blood donors had an elevated ALT [3] while their HBV carrier rate was 0.2-0.59'0 [4]; in Sardinia these rates were 4 and 3%, respectively [5]. However, since blood units with elevated ALT levels cause PTH more often than those with normal ALT [3], it appears important to determine the role of testing of ALT and other surrogate markers in areas with intermediate and high HBV carrier rates.…”
Section: Introductionmentioning
confidence: 99%
“…1.3-12% of donations, less than a third of which may be infective) might prevent about 30% of PTH [ 1 4 , 10-151. Doubts have been expressed as to whether this expectation has been fulfilled (5,16,171 and this has been difficult to assess in the absence of prospective studies. In countries with low endemic rates of nonA, nonB hepatitis, it has been suggested that ALT screening may be of minimal benefit with most ALT elevations being due to non-viral causes such as obesity [12,15] or failure to apply appropriate cutoff levels for the differences that occur between sexes [3,4,.…”
Section: Discussionmentioning
confidence: 99%
“…Concern has also been expressed over the potential impact on donor deferral or exclusion rates of serial ALT testing of long-standing or frequently donating donors. If ALT elevation is an essentially random event, rather than occuring consistently in a few identifiable donors, it has been estimated that up to 50% of a donor panel might be lost over a 10-year-period for groups such as plasmapheresis donors who give blood frequently [5]. The limited duration studies that have been performed to date indicate persistent ALT elevation in 25-66%, and intermittent elevation of 30-80% of such donors [4,5,14,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation